Psychometric properties of the Social and Emotional Learning Scale: Social Skills Improvement System (SSIS SEL) - Alquwaie, Norah Abdulaziz; Alwatban, Mohammad Sulaiman (Journal of Educational and Psychological Sciences, 2025)
This study aimed to validate the Social and Emotional Learning Scale: Social Skills Development System, an instrument designed to measure social and emotional learning (SEL) in educational settings (Gresham & Elliott, 2008). (677) secondary school students in Hail completed (SSIS SEL). The study approach is the descriptive. The methodology comprised two primary analytical procedures: an evaluation of the scale's internal consistency using Cronbach's alpha and the Weighted Omega coefficient, and a confirmatory factor analysis to assess the model fit of the scale's structure. The results revealed that the scale exhibited high internal consistency, with a Cronbach's alpha coefficient of (0.934) and a Weighted Omega coefficient of (0.933). The confirmatory factor analysis confirmed the five-factor structure of the scale, with each dimension meeting the quality criteria for model fit. In conclusion, this study supports the Social and Emotional Learning Scale: Social Skills Development System as a valid and reliable tool for assessing SEL in educational settings. Future studies are recommended to investigate the scale's applicability across different cultural contexts and its relationship with other educational outcomes.
Keywords: Social and Emotional Learning; Confirmatory Factor Analysis; Social Skills Development